Case report: Novel treatment regimen for enterovirus encephalitis in SCID - Chetty, Kritika; Cheng, Iek; Kaliakatsos, Marios; Gonzalez-Granado, Luis Ignacio; Klapsa, Dimitra; Martin, Javier; Bamford, Alasdair; Breuer, Judith; Booth, Claire (Frontiers in Immunology, 2022)
Most non-polio enterovirus infections in immunocompetent individuals are acute and self-limiting in nature, however infection can be severe, chronic and have devastating outcomes in immunocompromised hosts. Therapeutic strategies have predominantly involved supportive care, with the lack of approved antiviral treatments proving challenging for management. We report a case of an 8-month-old who presented with severe enterovirus encephalitis following gene therapy for X-SCID, who demonstrated clinical and microbiological improvement after a novel regimen of favipiravir, fluoxetine and high dose IVIg. The patient presented 6 weeks post gene therapy with rapid neurological deterioration in the context of incomplete immune reconstitution, with microbiological and radiological evidence confirming enterovirus encephalitis. His neurology stabilised 8 weeks after treatment, and he subsequently demonstrated excellent immune recovery. This is the first case report of combined therapy with favipiravir, fluoxetine and high dose IVIg in the context of severe enterovirus encephalitis in an immunocompromised host. This case highlights the importance of considering enterovirus encephalitis in immunocompromised patients presenting with both acute and chronic neurological signs, as well as developmental regression. The demonstrated treatment success and the associated low risk of toxicity warrants further investigation of this therapeutic regimen.